A new species of Dibamus from the Central Highlands of Vietnam with redescription of Dibamus montanus Smith, 1921 (Squamata: Dibamidae) - Kliukin, Nikita S.; Nguyen, Tan Van; Pawangkhanant, Parinya; Pham, Hieu Minh; Le, Son Xuan; Gorin, Vladislav A.; Bos, Collin; Krone, Isaac W.; Poyarkov, Nikolay A. (Zootaxa, 2025)
The Langbian Blind Skink, Dibamus montanus Smith, 1921, was described more than 100 years ago based on two specimens from Langbian Plateau, southern Vietnam. Herein, we provide a revised diagnosis of D. montanus based on re-examination of the type series and two additional specimens collected during our recent field survey in Lam Dong Province, southern Vietnam. Furthermore, we describe a new species of dibamid lizard based on a single specimen collected from Kon Ka Kinh National Park, Gia Lai Province, central Vietnam, which was previously confused with D. montanus. We present an updated genealogy for the family Dibamidae based on three mitochondrial genes (16S rRNA, ND2, and COI) and demonstrate that D. montanus and the Gia Lai specimen form two deeply divergent matrilines with sequence divergence p = 18.6% in the ND2 gene and p = 6.4% in the 16S rRNA gene. The new species Dibamus annae sp. nov. can be readily distinguished from D. montanus and other congeners by the following combination of morphological characters: labial and nasal sutures present and complete; rostral suture present and incomplete; three scales posterior to interparietal; maximum SVL of 92.7 mm; tail comparatively long, TL comprising 18.9% of SVL in a single male; two scales bordering the posteromedial edge of the first infralabial; the medial sublabial scale not enlarged; 19 midbody scale rows; 21 transverse scale rows just posterior to head; 18 transverse scale rows just anterior to vent; 180 ventral scales; 45 subcaudal scales; relative size of frontal to frontonasal 136.3%; relative size of interparietal to nuchal scale 133.9%. Our study brings the total number of species in the genus Dibamus to 28; Dibamus annae sp. nov. is the ninth species of Dibamus recorded from Vietnam, which further highlights the importance of this country as a center of reptilian diversity in Southeast Asia. We also provide an identification key for the species of Dibamus that occur in Indochina.